Double Duty: SGLT2 Inhibitors as Cardioprotective and Anticancer Allies - Linda Piras; Michela Zuccanti; Giacomo Tini Melato; Massimo Volpe; Giuliano Tocci; Emanuele Barbato; Allegra Battistoni (Hearts)
Sodium glucose cotransporter-2 inhibitors (SGLT2i), originally developed for type II diabetes mellitus, have recently been approved for the treatment of heart failure in both diabetic and non-diabetic patients due to their significant cardiovascular benefits. Beyond their established role in diabetes and heart failure management, current research is exploring the potential applications of SGLT2 inhibitors in the field of cardio-oncology. This interest is driven by dual possible benefits: cardioprotection against the adverse effects of antitumor therapies and inherent antitumor properties. Patients affected by cancer often face the challenge of managing cardiovascular toxicity induced by antineoplastic treatments. SGLT2 inhibitors have shown promise in mitigating toxicities, thereby enhancing the cardiovascular health of these patients. Additionally, emerging evidence suggests that SGLT2 inhibitors may possess direct antitumor effects, further contributing to their therapeutic potential in oncology. This review aims to provide a comprehensive overview of the molecular mechanisms through which SGLT2 inhibitors exert their cardioprotective and antitumor effects. Furthermore, we will examine the current body of evidence supporting the use of these inhibitors in a cardio-oncology setting.